2023
DOI: 10.31635/ccschem.022.202101757
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Transmetallation in Electric Potential-Promoted Oxidative Coupling in a Single-Molecule Junction

Abstract: To monitor and investigate chemical reaction in real-time and in situ is a long-standing and challenging goal in chemistry. Herein, an electric potential-promoted oxidative coupling reaction of organoboron compounds without the addition of base is reported, and the transmetallation process involved is monitored in real-time and in situ with STMBJ technique. We found the electric potential applied determined the transmetallation. At low bias voltage, the first-step transmetallation process occurred and afforded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…While different boron-containing molecules have been studied using the STM-BJ method, 44−49 it has recently been reported that arylboron-based compounds can undergo electric fieldinduced 50−52 transmetalation reactions at gold surfaces in the presence of oxygen and water to form covalent aryl-Au linked single-molecule junctions. 53 We therefore propose that the feature observed at ∼10 −2 G 0 in our measurements may originate from junctions formed from MeS-BO (generated by the hydrolysis of BN and BO) or by direct aryl-B transmetalation from the intact compounds. Notably, the 1 H NMR spectra of BN and BO solutions exposed to air for up to 7 days (Figure S38), or for a BO solution stirred in air with Au powder (<10 μm diameter) for ∼2 h (Figure S39), 54 reveal no signs of significant decomposition.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…While different boron-containing molecules have been studied using the STM-BJ method, 44−49 it has recently been reported that arylboron-based compounds can undergo electric fieldinduced 50−52 transmetalation reactions at gold surfaces in the presence of oxygen and water to form covalent aryl-Au linked single-molecule junctions. 53 We therefore propose that the feature observed at ∼10 −2 G 0 in our measurements may originate from junctions formed from MeS-BO (generated by the hydrolysis of BN and BO) or by direct aryl-B transmetalation from the intact compounds. Notably, the 1 H NMR spectra of BN and BO solutions exposed to air for up to 7 days (Figure S38), or for a BO solution stirred in air with Au powder (<10 μm diameter) for ∼2 h (Figure S39), 54 reveal no signs of significant decomposition.…”
mentioning
confidence: 67%
“…Control experiments reveal that the conductance feature observed in each measurement at ∼10 –2 G 0 results primarily from the same junctions formed by 4-(methylthio)­phenylboronic acid ( MeS-BO ), a common hydrolysis product of both compounds (see the SI for more details). While different boron-containing molecules have been studied using the STM-BJ method, it has recently been reported that arylboron-based compounds can undergo electric field-induced transmetalation reactions at gold surfaces in the presence of oxygen and water to form covalent aryl-Au linked single-molecule junctions . We therefore propose that the feature observed at ∼10 –2 G 0 in our measurements may originate from junctions formed from MeS-BO (generated by the hydrolysis of BN and BO ) or by direct aryl-B transmetalation from the intact compounds.…”
mentioning
confidence: 68%
“…In the past few decades, great progress has been achieved in molecular electronics assisted by the development of break junction techniques such as mechanically controllable break junctions (MCBJs), scanning tunneling microscopy (STM) break junctions, and other techniques. To measure the conductance of a single molecule, it is necessary to connect the molecule to metallic electrodes. Therefore, anchoring groups play a crucial role in fabricating a metal–molecule–metal (M–M–M) junction.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transport in the single molecule-junction is at the heart of molecular electronics. [1][2][3][4][5][6][7][8][9][10][11] The molecule/electrode interface has severe impact on the charge transport and functioning of the single-molecule junction. The common strategies to tune the molecule/electrode interface are to change the electrodes or the anchoring group of molecules.…”
mentioning
confidence: 99%